E-portafolios.-La búsqueda de un software coherente con la propuesta de enseñanza - Fernando Fraga Varela; Adriana Gewerc Barujel (Universitat Politècnica de València, 2011)
RESUMEN Multimedia languages offer us the possibility of connecting our students´ learning with new digital languages while enhancing the processes of knowledge acquisition. We particularly focus on the value of audiovisual narratives in the reflexive teacher training, as a facilitative tool to comprehend and aprehend the educational reality. In this article we describe the elaboration and use of the portfolio as a bionarrative tool, and its context of use, its formats, its scaffoldings and possibilities, within the Project on Educational Innovation Elkarrikertuz (collaborative inquiry). ABSTRACT In this paper, we describe the e-portfolio as a tool which makes it possible to put together an education proposal that fulfils the new universities demands in general and a teacher education for the needs imposed by information and knowledge society.  In that context, we emphasize the analysis of the process of finding software allows us to pursue our goals. This is shown in the need to locate technology resources tailored to the educational needs, also transforming them into the context of the practice located. Has been selected and adapted software (Elgg) working on the need to recognize the prominence of the subject and their individuality in the organization of their own learning (Personal Learning Environment-PLE-).